Motivasi Belajar Bahasa Mandarin Murid Kelas II SMP Sekolah Minggu Buddha Maitreya Medan - Elly Romy; Nuryadi Nuryadi (Journal of Language, Literature and Teaching, 2019)
This research was aimed at explaining the learning motivation of the second grade of Junior High School students at Sekolah Minggu Buddha Maitreya Medan in learning Mandarin. Besides, the goal of this research was to describe the factors that influence their learning motivation. This study was conducted by using descriptive qualitative design. The subjects of this study was 20 students of the second grade of Junior High School students at Sekolah Minggu Buddha Maitreya. Motivation is divided into intrinsic and extrinsic motivation. Thus, the study of the students’ learning motivation was separated according to the type of motivation. The results showed that there were about 8 students that had intrinsic motivation, while there were about 11 students that had extrinsic motivation. The factors that underlie this finding was due to the difficulty that the students faced in learning Mandarin.